Investigation of 2D Boridene from First Principles and Experiments. (5th January 2022) - Helmer, Pernilla; Halim, Joseph; Zhou, Jie; Mohan, Roopathy; Wickman, Björn; Björk, Jonas; Rosen, Johanna
Abstract: Recently, a 2D metal boride – boridene – has been experimentally realized in the form of single‐layer molybdenum boride sheets with ordered metal vacancies, through selective etching of the nanolaminated 3D parent borides (Mo2/3 Y1/3 )2 AlB2 and (Mo2/3 Sc1/3 )2 AlB2 . The chemical formula of the boridene was suggested to be Mo4/3 B2‐ x T z, where T z denotes surface terminations. Here, the termination composition and material properties of Mo4/3 B2‐ x T z from both theoretical and experimental perspectives are investigated. Termination sites are considered theoretically for termination species T = O, OH, and F, and the energetically favored termination configuration is identified at z  = 2 for both single species terminations and binary termination mixes of different stoichiometries in ordered and disordered configurations. Mo4/3 B2‐ x T z is shown to be dynamically stable for multiple termination stoichiometries, displaying semiconducting, semimetallic, or metallic behavior depending on how different terminations are combined. The approximate chemical formula of a freestanding film of boridene is attained as Mo1.33 B1.9 O0.3 (OH)1.5 F0.7 from X‐ray photoelectron spectroscopy (XPS) analysis which, within error margins, is consistent with the theoretical results. Finally, metallic and additive‐free Mo4/3 B2‐ x T z shows high catalytic performance for the hydrogen evolution reaction, with an onset potential of 0.15 V versus the reversible hydrogen electrode. Abstract : The 2D boridene, Mo4/3 B2‐ x T z, is investigated with respect to surface terminating species and basic electronic properties, using both experimental and theoretical methods. The theoretical results are consistent with experiments and suggest a possibility for tailoring of the electronic properties. The boridene also shows high catalytic performance for the hydrogen evolution reaction.